Effects of floral therapy on labor and birth: a randomized clinical trial - Sonia Regina Godinho de Lara; Maria Cristina Gabrielloni; Mônica Bimbatti Nogueira Cesar; Márcia Barbieri (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to assess the effects of floral therapy in the face of factors that boost pain in the parturition process and its results in the duration of labor. Methods: this is a randomized, controlled and triple-blind clinical trial. We selected 164 pregnant women with gestational age ≥37 weeks, cervical dilation ≥4 cm, randomly divided into floral therapy and placebo group. Results: the Five Flower floral essence proved to be effective, considering the factors that boost pain in labor. Experimental Group did not show an increase in contractions, unlike Control Group, which presented an increase of one contraction for mothers in active phase and amniorrhexis. The Five Flower essence proved to be effective in reducing labor time by 1:30h from the beginning of the intervention at birth. Conclusions: floral therapy proved to be effective in pain management, reflecting positively in its brevity, qualifying its outcome.